The Influence of Investment and Minimum Wages on Labor Absorption in Gresik Regency - Abdillah, Abdillah; Iswati, Iswati (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2024)
Researchers want to understand the effect of investment on employment in Gresik Regency; and also the effect of the minimum wage on employment in Gresik Regency; and how the influence of investment and minimum wage together on employment in Gresik Regency. The research method used is quantitative. As well as for the population it is the entire development of investment, minimum wage and labor force in Gresik Regency in 2018-2022. And for the sample, the researcher used the total sampling technique. As for the data obtained by documentation techniques and literature study. After that, multiple regression analysis can be carried out using this analysis, the researcher gets the same results for the X1 investment variable, which has an influence on the Y variable on labor absorption, and for the X2 variable, and the minimum wage X2 also has an influence on the Y variable on labor absorption